Impact of fetal chromosomal disorders on maternal blood metabolome: toward new biomarkers? - Pinto, Joana
OBJECTIVE: This study aimed at determining the relationship between fetal chromosomal disorders (CDs), including trisomy 21 (T21), and on first-and second-trimester maternal blood plasma, to identify the time-course metabolic adaptations to the conditions and the possible new plasma biomarkers. Furthermore, a definition of a joint circulatory (plasma) and excretory (urine) metabolic description of second-trimester CDs was sought. STUDY DESIGN: Plasma was obtained for 119 pregnant women: 74 controls and 45 CD cases, including 22 T21 cases. Plasma and lipid extracts (for T21 only) were analyzed by nuclear magnetic resonance spectroscopy, and data were handled by variable selection and multivariate analysis. Correlation analysis was used on a concatenated plasma/urine matrix descriptive of second-trimester CD, based on previously obtained urine data. RESULTS: CD cases were accompanied by enhanced lipid beta-oxidation (increased ketone bodies) and underutilization of glucose, pyruvate, and citrate. Lower circulating high-density lipoprotein levels were noted, along with changes in the proline and methanol in the first trimester, and also the urea, creatinine, acetate, and low-density lipoprotein plus very low-density lipoprotein in the second trimester and the different urea and creatinine levels, suggesting fetal renal dysfunction. In terms of plasma composition, T21 cases were indistinguishable from other CDs in the first trimester, whereas in the second trimester, increased methanol and albumin may be T21 specific. Furthermore, first-trimester lipid extracts of T21 showed decreased levels of 18: 2 fatty acids, whereas in the second trimester, lower levels of 20: 4 and 22: 6 fatty acids were noted, possibly indicative of inflammation mechanisms. In both trimesters, high classification rates for CDs (88-89%) and T21 (85-92%) generally relied on variable selection of nuclear magnetic resonance data. Plasma/urine correlations confirmed most metabolic deviations and unveiled possible new ones regarding low-density lipoprotein plus very low-density lipoprotein, sugar, and gut-microflora metabolisms. CONCLUSION: This work partially confirmed previously reported data on first-trimester T21 and provided additional information on time-course metabolic changes accompanying CD and T21, in particular regarding plasma lipid composition. These results demonstrate the potential of plasma metabolomics in monitoring and characterizing CD cases; however, validation in larger cohorts is desirable.